Imagens da Arte - Maria Filomena Borja de Melo (Medievalista)
What is the discourse about art and aesthetic in late Middle Age? Before Kant, before contemporary art critics, before a systematic reflexion about art, how was it to talk about art subjects, about beauty, about the art works that were done around? What and how was it seen and what was ignored?The purpose of the thesis, which resume is presented hear, was to find a few answers to those and other related questions, beginning by finding the ways to the answers. If working without specific art texts, it was first necessary to select alternative sources to supply information. Different kinds of texts were chosen, in order to arrive to some guidelines that leaded to common and coherent references about philosophic conceptions, art vocabulary, aesthetic emotions, art as a work, and so on. Among some waited answers, a few surprises also. Beauty is Good, because Good is God. So beauty must be God’s image in number, proportion, equilibrium, harmony, greatness and light. Rich materials where in the way of beauty and, at least interested a lot the writers, on those days. Other specific conclusion was that something known was something safe, so difference and peculiarity were not a aim to achieve. As well, the owners, those who proceeded or ordered were more appreciated than the artists or art workers. Short, it was much more important to do something, and do it well, than to care how and who did: that was, more or less, what Saint Thomas claimed.